The Influence of Social Media Promotion, Service Quality, Branding, and Price on Consumer Satisfaction in RM. Delicious Foods in Palopo City - Nurpadilla; Edi Maszudi; Andi Rizkiyah Hasbi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The increasingly tight culinary business competition in Palopo City forces business actors, including RM. Serba Nikmat, to innovate in promoting their businesses through social media. Although digital promotion has been intensified, this restaurant still receives various responses from consumers regarding the service, brand perception, and prices offered. This phenomenon shows that the success of a culinary business is not only determined by how intensively the promotion is carried out, but also by the quality of service, branding strength, and the suitability of prices to consumer expectations. This study aims to determine the effect of Media Social Promotion, Service Quality, Branding, and Price on Consumer Satisfaction at RM. Serba Nikmat in Palopo City. The research population is the number of all consumers at RM. Serba Nikmat. The study uses a quantitative approach with a sample of 10 times the number of measurement items. With 23 indicators, the minimum sample obtained is 230. Data analysis uses SPSS 22 statistical analysis. The results of the study show; Media Social Promotion has a positive and significant effect on consumer satisfaction, Service Quality has a positive and significant effect on consumer satisfaction, Branding has a positive and significant effect on consumer satisfaction, Price and the four variables simultaneously affect consumer satisfaction.